If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -29 = 36 Reorder the terms: -29 + 6b = 36 Solving -29 + 6b = 36 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 6b = 36 + 29 Combine like terms: -29 + 29 = 0 0 + 6b = 36 + 29 6b = 36 + 29 Combine like terms: 36 + 29 = 65 6b = 65 Divide each side by '6'. b = 10.83333333 Simplifying b = 10.83333333
| 4x^2-13x+5=-5x+2 | | x^2+5x+17=-5x+1 | | 3d-9-8b=11 | | x^2+7x-1=7 | | n^4-13n^2+36=0 | | 5g*4d= | | 11-8x=0 | | x^2+10x-27=8x-3 | | 5x-33=2x+57 | | =0.4(3d-5) | | -2y+3(-2)+5y+35=6y+2(-2)-3y+8 | | 2x+9y=4 | | 2(-2)-3+5y+6=8y-4(-2)+24 | | 3x+7y=6 | | 9(x-2)-4=14 | | -9x+3+5x=2x-3x+3+7-2 | | -x-2y+z=-6 | | 3x/7-5=4 | | 9(x-1)+3x=-9x+5 | | 2x+4y-2z=6 | | 0.42x-5=4 | | x+3y-z=12 | | 5x-y+5z=30 | | 5x-2x+6-4+14=5x-3x+8 | | 3(g-7)-2=4 | | 16=-4-4x | | -x+2y-3z=-9 | | -3t+5=26 | | 4x-2x+3-8=7x-5+4x | | 3t+5=26 | | (x^2+y^4)(x^2-y^4)=0 | | 0.67x+7=21 |